MUTU ORGANOLEPTIK DAN NILAI GIZI CRACKERS KOMBINASI TEPUNG BUAH LINDUR (Bruguiera gymnorrhiza) DAN TEPUNG TEMPE - MADE MITA DWI SARASWATI, 101414153022 (2016)
Utilization of functional foods more intensively to do until today. Making cracker by utilizing functional foods such as lindur fruit and tempeh could be used as an alternative snack for people with diabetes. The purpose of this study are to determine the level of preference such as color, aroma, texture and taste on three cracker products, and also the nutritional value differences on three cracker products with a combination of flour from lindur fruit and tempeh. This research is an experimental research which directed on developing products. The study involved 5 limited panelists and 30 untrained panelists from the people with diabetes. Kruskal-Wallis test showed that based on level of preference there were differences in taste (0.001) and color (0.002) among three cracker products. Further tests by Mann-Whitney test showed that there is no difference in color between f1 and f2 cracker products (0.252), also there is no difference in taste between f2 and f3 cracker products (0.266). The most favored cracker by all the panelists was f1 cracker product. Laboratory analysis on nutrient content showed that there is no significant differences between three cracker products (0.996). Cracker with highest nutritional value is f1 product cracker. Conclusion: There are differences on color and taste among three cracker products. There is no differences on nutritional value on each cracker. The most optimal cracker formulas is f1.